Next-generation Trade Facilitation for Asian Integration: Cross-border Paperless Trade. Issue 1 (April 2019) - Duval, Y.; Wang, T.; Utoktham, C.; Kravchenko, A.
Abstract: Reducing trade costs is essential to achieve Asian integration. Trade costs in the Asian and the Pacific region remain high, in particular, between different Asian subregions. Significant progress has been made in implementation of trade facilitation measures between 2015 and 2017, particularly those included in the World Trade Organization (WTO) Trade Facilitation Agreement (TFA). However, progress in implementing of next-generation digital trade facilitation measures, such as cross-border paperless trade measures, has been more limited. Simulation results suggest that full implementation of such measures could nearly double trade costs reductions expected from WTO TFA implementation. A new regional United Nations (UN) treaty, the Framework Agreement on Facilitation of Cross-Border Paperless Trade in Asia and the Pacific, may accelerate progress in this area. JEL Codes: F13, F15, F17